CD24 is a genetic modifier for risk and progression of prostate cancer - Zhang, Yifan; Li, Bingjin; Zhang, Xingyi; Sonpavde, Guru P.; Jiao, Kenneth; Zhang, Andrea; Zhang, Guangxin; Sun, Mei; Chu, Chengjing; Li, Feng; Wang, Lizhong; Cui, Ranji; et al. (Molecular carcinogenesis, 2017)
CD24 plays an oncogenic role in the onset and progression of various human cancers, including prostate cancer. In the present study, we identified two linkage disequilibrium blocks with four recombination hotspot motifs in human CD24 locus. To elucidate whether genetic variants of CD24 are associated with susceptibility to prostate cancer and its disease status, we conducted a case‐control association study with two P170 C/T and P‐534 A/C polymorphisms of CD24 in 590 patients with prostate cancer and 590 healthy controls. A significant increased risk of prostate cancer was found in men with the P170T/T genotype over the P170C/C genotype (odd ratio = 1.74, 95% confidence interval = 1.16–2.63, P = 0.008), and in men with the P‐534C/C genotype over the P‐534A/A genotype (odd ratio = 1.47, 95% CI = 1.18–2.26, P = 0.003). Cochran–Armitage trend analysis showed that the P170T allele was significantly correlated with an increased risk of prostate cancer progression (P = 0.029, trend between genotypes and stages) and this observation was also validated in an independent sample cohort. Next, we found that tumors with P170T or P‐534C alleles had more twofold increased protein expressions of CD24 as compared to those with P170C or P‐534A alleles, respectively. Likewise, tumors with a combination of P170T/T and P‐534C/C genotypes were associated with a high mRNA level of CD24. Our data suggest a significant association of CD24 genetic variants with prostate cancer onset and progression, which provides new insight into molecular genetics of prostate cancer; however, these findings need to be validated in multiple independent cohorts. © 2016 Wiley Periodicals, Inc.